ALKBH5-mediated m6A demethylation of KCNK15-AS1 inhibits pancreatic cancer progression via regulating KCNK15 and PTEN/AKT signaling - Yuan He (Nature Publishing Group, 2021)
Abstract Long noncoding RNAs (lncRNAs) are regarded as crucial regulators in tumor progression. Potassium two pore domain channel subfamily K member 15 and WISP2 antisense RNA 1 (KCNK15-AS1) has been confirmed to inhibit the migration and invasion of pancreatic cancer (PC) cells. However, its downstream mechanism and effect on other cellular functions in PC remain unknown. This study probed the function and potential mechanism of KCNK15-AS1 in PC cell growth. RT-qPCR and western blot were employed to measure gene expression in PC cells. ISH was applied to analyze KCNK15-AS1 expression in PC tissues. Functional assays were utilized to evaluate PC cell proliferation, apoptosis, migration and EMT. Mechanical experiments were adopted to detect gene interaction in PC cells. The obtained data indicated that KCNK15-AS1 was down-regulated in PC cells and tissues. Overexpressing KCNK15-AS1 hindered cell proliferation, migration and EMT while facilitated cell apoptosis in PC. Mechanically, alkylation repair homolog protein 5 (ALKBH5) was verified to induce m6A demethylation of KCNK15-AS1 to mediate KCNK15-AS1 up-regulation. KCNK15-AS1 combined with KCNK15 5’UTR to inhibit KCNK15 translation. Moreover, KCNK15-AS1 recruited MDM2 proto-oncogene (MDM2) to promote RE1 silencing transcription factor (REST) ubiquitination, thus transcriptionally upregulating phosphatase and tensin homolog (PTEN) to inactivate AKT pathway. In conclusion, our study first confirmed that KCNK15-AS1 hinders PC cell growth by regulating KCNK15 and PTEN, suggesting KCNK15-AS1 as a potential biomarker of PC.